2022
DOI: 10.1037/hea0001155
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among oncologists and oncology nurses: A systematic review and meta-analysis.

Abstract: Background: Significant proportions of burnout have been reported among both oncologists and oncology nurses. However, these groups have not been compared in a meta-analytic design. It is important to compare how burnout affects different types of health professionals to understand its individual implications and devise ways of minimizing and treating it. Objective: The current meta-analysis study aimed to systematically compare burnout prevalence between oncologists and oncology nurses. Method: Authors assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
1
12
0
3
Order By: Relevance
“…These results are recorded in the third column of Tables 4-6. From Table 4, it can be inferred that the rate of improvement in terms of having a quality life was greater for those who were in the intervention group, with a p-value of 0.0007, which is almost in line with existing studies (21,22,29,32). Nevertheless, the attention control group also performed better in terms of having a quality life as the time progressed, with many interventions.…”
Section: Findings and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are recorded in the third column of Tables 4-6. From Table 4, it can be inferred that the rate of improvement in terms of having a quality life was greater for those who were in the intervention group, with a p-value of 0.0007, which is almost in line with existing studies (21,22,29,32). Nevertheless, the attention control group also performed better in terms of having a quality life as the time progressed, with many interventions.…”
Section: Findings and Discussionsupporting
confidence: 81%
“…In fact, these factors certainly affect the hope of an individual. Certain studies identified that the element of hope was higher among those patients who experienced lower levels of anxiety and depression, along with higher levels of social, emotional, and financial support (20)(21)(22). Therefore, such patients could have a better quality of life when compared with those who have higher levels of anxiety and depression and low levels of social, emotional, and financial support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on occupational health rather than on individual HCP’s mental health moves the problem and the solutions to the structural conditions of practicing oncology, rather than on the individual physician. We see this as a positive development in the HCP literature since many studies have found that a quarter to three quarters of oncology HCPs report feeling burned out and that this issue has become worse as a result of the pandemic [ 72 , 73 , 74 ]. These high numbers suggest that the factors that contribute to burnout are widespread and have to do with the nature of the work and environmental concerns, rather than the problem of individual HCPs and that changes are needed within the profession to help reduce this problem.…”
Section: Discussionmentioning
confidence: 95%
“…We agree with these recommendations and see them as an important first step in improving oncology HCPs’ quality of life. Burnout is a critical factor to consider when it comes to HCP well-being both pre- and post-pandemic, and as noted above, much has been written on how to reduce burnout among oncology HCPs [ 8 , 25 , 36 , 50 , 74 ]. However, our review also found gaps in our understanding and knowledge on the mental health of oncology HCPs, as well as a limited set of recommendations on how to improve this situation.…”
Section: Discussionmentioning
confidence: 99%